2010
DOI: 10.1262/jrd.09-117e
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Activities of Neurones in the Dorsomedial Hypothalamic Nucleus Projecting to the Supraoptic Nucleus During Milk-ejection Reflex in the Rat

Abstract: Abstract. Using urethane-anesthetized lactating rats, extracellular action potentials were recorded from single cells in the dorsomedial hypothalamus (DMH), which were identified as projecting to the supraoptic nucleus (SON). Sixty-two DMH cells were identified as projecting to the SON. Of these 53, 4 and 5 cells had ipsilateral, contralateral and bilateral projections, respectively. Two cells (1 ipsilaterally and 1 contralaterally projecting cell) showed bursting activities preceding milk ejection that were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…In addition to our previous results indicating that some DMH cells projected to the SON in both sides of the hypothalamus [11,12,13], the results of the present experiment suggesting the existence of excitatory connections between OT cells in the bilateral hypothalamus would be a good base supporting a synchronization of burst discharges of OT cells in separate magnocellular nuclei.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In addition to our previous results indicating that some DMH cells projected to the SON in both sides of the hypothalamus [11,12,13], the results of the present experiment suggesting the existence of excitatory connections between OT cells in the bilateral hypothalamus would be a good base supporting a synchronization of burst discharges of OT cells in separate magnocellular nuclei.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous studies on the DMH showed that the cells in the DMH on one side projected to the SON in both sides of the hypothalamus. However, there were not many cells in the DMH projecting to the SON in both sides of the hypothalamus [11,12,13]. So it seems unlikely that such a small number of DMH cells fully support synchronization of 9000 OT cells in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takano et al 151 recorded hypothalamic neurons near the PVN during the reflex, all of which could be antidromically identified from ipsilateral SON stimulation but did not project to the neurohypophysis. 152,153 Even though the antidromic DMH projections to the region of the SON are more strongly ipsilateral, 142 DMH stimulation can activate the SON bilaterally. Electrical stimulation of the DMH facilitates OT neuronal activity in the SON.…”
Section: Hypothalamic Circuitrymentioning
confidence: 99%